The study of antiosteoporotic action of nanoparticulated resveratrol and losartan - N. U. Koklina; O. S. Gudyrev; A. V. Faitelson; M. V. Pokrovskiy (Кубанский научный медицинский вестник, 2014)
The study demonstrated that eight weeks after ovariectomy in female white Wistar rats endothelial dysfunction of bone microvasculature and deterioration of regional blood flow in bone develops, leading to the emergence of generalized osteoporosis. Nanoparticulated forms of losartan and resveratrol, possessing endothelioprotective action, effectively prevents the reduction of regional microcirculation in bone tissue, keeping it at the level of intact rats. It is allowed to maintain an adequate level of bone remodeling processes, which manifested in slowing of the thinning of bone trabeculae and preventing the occurrence of their microfractures.